2020
DOI: 10.2147/idr.s274163
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antibiotic Resistance and <em>mecA</em> Gene Characterization of Coagulase-negative <em>Staphylococci</em> Isolated from Clinical Samples in Nepal</p>

Abstract: Background Coagulase-negative Staphylococci (CoNS) are a significant cause of hospital-acquired and foreign-body-related infections. We conducted this research to assess methicillin susceptibility of CoNS by disc diffusion, agar dilution, and polymerase chain reaction (PCR) methods and to assess the antimicrobial susceptibility pattern. Methods We received 123 CoNS isolates from different specimens including blood, endotracheal tube, and centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(23 reference statements)
3
9
4
Order By: Relevance
“…However, the study also demonstrated majority of isolates being susceptible to chloramphenicol (91.1%) and tetracycline (87.4%). Such high frequency of susceptibility pattern of chloramphenicol is consistent with the previous study by [ 24 , 33 , 36 , 37 ], but their study showed lower susceptibility in case of erythromycin and penicillin. Indeed, similar susceptibility profile for all CNS strains was found as that of S. epidermidis strains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the study also demonstrated majority of isolates being susceptible to chloramphenicol (91.1%) and tetracycline (87.4%). Such high frequency of susceptibility pattern of chloramphenicol is consistent with the previous study by [ 24 , 33 , 36 , 37 ], but their study showed lower susceptibility in case of erythromycin and penicillin. Indeed, similar susceptibility profile for all CNS strains was found as that of S. epidermidis strains.…”
Section: Discussionsupporting
confidence: 92%
“…S. saprophyticus along with blood and wound/pus was also isolated from urine. The high number of S. saprophyticus in urine is consistent with the previous studies [ 24 , 35 ] may be due to its adhering capacity to wall of urinary tract. Importantly, all CNS species were isolated from different medical devices indicating their ability to cause device associated infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 1 , 2 Methicillin resistance in S. aureus is mediated through an altered protein called low-affinity penicillin-binding protein (PBP2a) which is encoded by the mecA gene which is present in a chromosomal mobile genetic element called Staphylococcal cassette chromosome. 3 - 5 The most recent data regarding MRSA incidence obtained from WHO reported values exceeding 20% in all WHO regions, and even 80% in some countries. 6 MRSA is frequently resistant to most of the commonly used antimicrobial agents including aminoglycosides, macrolides, chloramphenicol, tetracycline, and fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…The principle drug resistance gene in MRSA strains is mecA, which is also known to exist in coagulase-negative Staphylococci (CoNS). 8 In addition, MRSA carrying the mecC gene has also been reported. 9 The common colonization sites of MRSA are the nasal vestibule, pharynx, gastrointestinal tract, and axilla.…”
Section: Introductionmentioning
confidence: 99%